Labor market volatility in the meat processing sector - LaPorchia A. Collins; Barry K. Goodwin; A. Ford Ramsey (Agricultural and Resource Economics Review)
We consider the effect of labor market volatility on employment and wages in the meat processing sector. The period of study includes the COVID-19 pandemic, which resulted in significant labor market shocks in the sector. We examine the relationship between historical volatility of employment and wages and current employment and wages, focusing on the animal slaughtering and processing sector (NAICS 3116). We utilize county-level data to estimate dynamic panel data models of employment and wages. We find that historical volatility in both employment and wages had a significant negative impact on employment in the sector. In the case of wage volatility, we find that wages are higher following periods of significant wage volatility, suggesting that workers demand higher wages under conditions of market volatility. During COVID, smaller meat processors had lower levels of employment, but a small number of large processors had significantly higher levels of employment. In contrast, wages were higher after COVID-19 for almost all counties included in the analysis. In an aggregate sense, COVID tended to largely reduce employment but increase wages in the meat processing sector.